Penerapan Prinsip Pengelolaan Dana Desa dalam Mewujudkan Good Financial Goverment of Village - Andni, Riyan; Hidayah, Nurul (Jurnal Studi Pemerintahan dan Akuntabilitas, 2023)
Purpose: This study aims to examine and explain the relationship between variables that exist in social reality. Methodology: This study uses a qualitative approach that emphasizes the explanation and perception of every human behavior. Data analysis is inductive/qualitative, and qualitative research emphasizes its importance over generalizations. Results: The results of this study indicate that the principles of good governance are fulfilled in building accountability, accountability and transparency in Wates Village. This is reflected in the implementation of the accountability process that prioritizes accountability, Responsibility and Transparency. Limitations: the research time is very short so that this research is not deep enough to review the management of village funds Contribution: This research is beneficial for the village so that the management of village funds becomes Good Village Government Finance.